Keputusan Pengguna Transportasi Online: Persepsi Promosi, Harga, Kualitas Pelayanan, dan Kemudahan Layanan - Satria Mirsya Affandy Nasution; Asrizal Efendy Nasution; Muhammad Taufik Lesmana (JURNAL ILMIAH MANAJEMEN & BISNIS, 2023)
Purpose – To understand more deeply user decisions in the context of online transportation, this research aims to analyze the key factors that influence user decisions, including price, promotions, service quality and convenience.Method –Sampling was carried out using purposive sampling through an accidental technique, where the samples taken were coincidental but met the criteria, namely having a history of using online transportation applications, with a total sample of 200 people in the Medan City area. Data was collected through questionnaires and data analysis techniques using Structural Equation Modeling - Part Least Square (SEM-PLS).Findings – The analysis shows that the price, promotion and service quality variables partially have a positive and significant effect on consumer decisions to use Gojek in Medan. However, the convenience variable only significantly influences consumers' decisions to use the service.Originality (Novelty) –This research focuses on user decisions in the context of online transportation and an in-depth study of critical factors, such as price, promotion, service quality and convenience. Uniqueness is also seen in combining key variables and understanding the influence of convenience in online transportation.Implications – To improve consumer decisions to use online transportation, companies must focus on pricing strategies, promotions, and improving service quality. Even though convenience is insignificant, companies can still consider improving this aspect. These findings provide a basis for companies to design more effective marketing strategies according to consumer preferences.